A Case of Acute Promyelocytic Leukemia Presenting as Sternal Infiltrate - Bapat, Kalyani; Mansukhani, Dia; Khodaiji, Shanaz; Padate, Balkrishna; Dubey, Abha (Annals of Pathology and Laboratory Medicine, 2023)
Granulocytic sarcoma (GS) or myeloid sarcoma (MS) is a localized extramedullary tumor composed of immature myeloid cells which can develop de novo or concurrently with acute myeloid leukemia (AML), myeloproliferative disorders (MPN) or myelodysplastic syndrome (MDS). It can present before, along with or after the diagnosis of acute myeloid leukemia, MPN, MDS or may present as a manifestation of relapse in a previously treated AML patient. The occurrence of MS in an acute promyelocytic leukemia (APL) patient is a very uncommon clinical event especially as initial or primary presentation. APL is often associated with a life threatening coagulopathy making prompt diagnosis and initiation of therapy critical. Unusual clinical localization may lead to misdiagnosis, or delayed diagnosis and treatment. Hence being aware of such atypical presentations of APL is crucial. Here we report a patient with acute promyelocytic leukemia who presented with sternal infiltrate but without any systemic symptoms. The diagnostic challenges are of particular interest given the unusual clinical presentation along with atypical morphology of the abnormal promyelocytes.